Drafted and served Edward "Skip" Swain ; one citizen soldier's experiences in Vietnam - Banks, Stephen A. (Banks, 2013)
The book was donated by the author in 2013 and is a memoir of Edward "Skip" Swain about his personal experiences in Vietnam as an enlisted man
Includes bibliographical references (p. 302-316) and index
Keywords: Swain, Edward J., -- 1948-; Vietnamkrieg; Vietnam War, 1961-1975 -- Personal narratives, American; Soldiers -- New York (State) -- Buffalo -- Biography; Veterans -- New York (State) -- Buffalo -- Biography; Autobiografie